Changing Metabolism in Differentiating Cardiac Progenitor Cells—Can Stem Cells Become Metabolically Flexible Cardiomyocytes? - Malandraki-Miller, Sophia; Lopez, Colleen A.; Al-Siddiqi, Heba; Carr, Carolyn A. (Frontiers in Cardiovascular Medicine, 2018)
The heart is a metabolic omnivore and the adult heart selects the substrate best suited for each circumstance, with fatty acid oxidation preferred in order to fulfil the high energy demand of the contracting myocardium. The foetal heart exists in an hypoxic environment and obtains the bulk of its energy via glycolysis. After birth, the ‘foetal switch' to oxidative metabolism of glucose and fatty acids has been linked to the loss of the regenerative phenotype. Various stem cell types have been used in differentiation studies, but most are cultured in high glucose media. This does not change in the majority of cardiac differentiation protocols. Despite the fact that metabolic state affects marker expression and cellular function and activity, the substrate composition is currently being overlooked. In this review we discuss changes in cardiac metabolism during development, the various protocols used to differentiate progenitor cells to cardiomyocytes, what is known about stem cell metabolism and how consideration of metabolism can contribute towards maturation of stem cell-derived cardiomyocytes